The Quality of Family Planing Related to Long-Term Contraception Selection - Dian Putri Maulidya; Sri Hernawati; Isa Ma’rufi (Humanistic Network for Science and Technology (HNST), 2018)
The use of long-term contraceptive methods (MKJP) such as IUD, MOP / MOW and implants is less desirable for people in Jember Regency. Based on Women's Empowerment and Family Planning Agency of Jember in 2016, the highest MOW family planning service data was obtained by Patrang Public Health Center 51 acceptors and the lowest was Gumukmas 10. The various reasons for family planning acceptors did not choose MKJP because the community lacked information about MKJP, lack of synergy between medical personnel installing contraception, unwillingness to install implants into the body, and the quality of service for midwives was not optimal yet. The purpose of this research was to analyze the relation between the quality of family planning services, namely tangible, reliability, responsiveness, assurance, and empathy with the selection of long-term contraception in family planning acceptors in Patrang Health Center area and Gumukmas Health Center. Types of observational analytic research. The research design was cross sectional. The population was all family planning acceptors at Patrang Health Center 185, Gumukmas Health Center 193. The research sample was 378 respondents. The sampling technique used cluster random sampling. Data collection techniques used questionnaires, interviews, and observations. Data analysis used chi square test. Based on the results of the research there was a relations between the quality of family planning services, namely tangible, reliability, responsiveness, assurance, and empathy with the selection of long-term contraception in family planning acceptors in the work area of Patrang and Gumukmas Health Centers. Keywords: Service quality, Long-term family planning, Family planning acceptors